2017
DOI: 10.1016/j.tsf.2016.11.047
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pulse plating frequency and duty cycle on the microstructure and stress state of electroplated copper films

Abstract: In this work we studied the impact of pulse electroplating parameters on the cross-sectional and surface microstructures of blanket copper films using electron backscattering diffraction and x-ray diffraction. The films evaluated were highly (111) textured in the direction perpendicular to the film surface. The degree of preferential orientation was found to decrease with longer pulse on-times, due to strain energy driven growth of other grain orientations. Residual biaxial stresses were also measured in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The concentration of the leveling and brightening addition agents is incomparable with the concentration of the basic components of electrolyte, which causes their fast consumption and the need for the permanent control and correction of the composition of the electrolyte. In order to avoid the use of additives, various periodically changing regimes of electrodeposition, such as pulsating and reversing current regimes, were proposed for obtaining compact uniform coatings [8,[17][18][19][20]. The lower-porosity and fine-grained structure of deposits are achieved by the simple regulation of parameters constructing these regimes.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of the leveling and brightening addition agents is incomparable with the concentration of the basic components of electrolyte, which causes their fast consumption and the need for the permanent control and correction of the composition of the electrolyte. In order to avoid the use of additives, various periodically changing regimes of electrodeposition, such as pulsating and reversing current regimes, were proposed for obtaining compact uniform coatings [8,[17][18][19][20]. The lower-porosity and fine-grained structure of deposits are achieved by the simple regulation of parameters constructing these regimes.…”
Section: Introductionmentioning
confidence: 99%
“…For all the above-mentioned applications, good film quality at the micro-or nano-level is required, and electrodeposition processes are very suitable to reach it. In relation to the application of constant regimes of electrolysis, the improvement of the quality of Cu coatings, i.e., their morphological and structural characteristics, can be achieved by the application of electrodeposition at a periodically changing rate [14][15][16], and the addition of specific substances known as additives to the electroplating baths [17][18][19], or simply by the regulation of parameters of electrolysis including mixing of the electrolyte, finding of the optimal temperature for electrodeposition or balanced salt/acid contents when acidic baths are used [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…First, when the pulse power is turned ON, Cu 2+ ions move to the cathode, and W nanoparticles are driven to the cathode due to the adsorption of Cu 2+ ions. Due to the large specific surface area and surface energy of W nanoparticles, Cu 2+ ions preferentially reduce on the surface of W particles to form Cu nuclei [ 17 ]. Second, the Cu nuclei continuously grow to form a Cu coating during the forward pulse.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Li et al [ 16 ] have studied the effect of pulse electroplating on the surface roughness of electrodeposited nickel films. Marro et al [ 17 ] also found the influence of pulse plating process parameters on the morphology and stress state of Cu film. The results showed when compared with DC electroplating, the electrodeposition of Cu by pulse electroplating could lead to minimal porosity and superior strength.…”
Section: Introductionmentioning
confidence: 99%